Development of a Novel Drug Delivery System “Nanoemulfoam” for Topical Delivery of Terbinafine Hydrochloride as a Repurposed Therapy in Skin Cancer: Formulation, Optimization, In Vitro Characterization, Ex Vivo Transdermal Permeability, Cytotoxicity Studies, and In Silico Assessment - Abeer A. Musallam; Reem A. Aldeeb; Riham M. Mansour; Manar Abd El-karim Kassem; Doaa Fayez Saeed; Mahmoud A. Mahdy; Rana M. Abdelnaby; Hanan M. Elnahas; Tarek M. Ibrahim (Pharmaceuticals, 2025)
Background: Skin cancer has become a global health issue because of increasing exposure to environmental contaminants and UV radiation. Terbinafine hydrochloride (TRB), a broad-spectrum antifungal medication, has demonstrated notable anti-tumor properties in previous studies; however, its repurposing for skin cancer therapy remains underexplored. Objective: This study reports for the first time, the development of a new delivery system: a nanoemulsion (NE)–foam hybrid system, i.e., “nanoemulfoam” (NEF), designed to enhance the topical TRB delivery to the skin. The study applied this new hybrid system on TRB for managing skin cancer. Method: The TRB-loaded NEF was produced by loading TRB into a liquid NE. then this was incorporated into a liquid foam base and actuated into foam using a non-propellant mechanism. The NE was developed utilizing peppermint oil as the oil phase and Tween-20/ethanol as the surfactant/co-surfactant combination (Smix). The formulation underwent optimization using the D-optimal design that enabled the simultaneous evaluation of the impact of oil concentration and Tween 20 concentration in the Smix on the particle size (PS), zeta potential (ZP), and dissolution efficiency percent (DE%). Results: The optimal NE formula displayed a small PS of 186.60 ± 2.84 nm, ZP of −13.90 ± 0.99 mV, and DE% of 68.50 ± 1.78% (mean ± SD, n = 3). After incorporation into the foam system, the produced TRB-loaded NEF demonstrated a 7.43-fold increase in the drug transdermal flux in comparison with plain drug foam (p < 0.05). The TRB-loaded NEF showed no signs of inflammation or irritation when applied to abdominal rabbit skin, indicating its safety. The optimum formula exhibited a statistically significant 10-fold increase in cytotoxicity against A-431 skin cancer cells compared to TRB alone, along with a 1.54-fold increase in apoptosis (p < 0.05). Molecular docking studies targeting CDK2, a key regulator of cell proliferation and a known TRB target, revealed that TRB displayed highly favorable binding scores compared to the reference drug. Conclusions: The TRB-loaded NEF represents a promising nanotechnology-based approach for the topical treatment of skin cancer, supporting further investigation toward clinical translation.